Current medical diagnosis & treatment 2026 - Papadakis, Maxine A.; Rabow, Michael W.; McQuaid, Kenneth R. (McGraw Hill, 2026)
Medical Diagnosis & Treatment 2026 reflects the latest developments in medicine, guidelines, scientific literature, and more. Readers will find accurate, reliable, evidence-based coverage of more than 1,000 diseases and disorders along with a concise, yet thorough synopsis of diagnosis and treatment. This trusted classic covers all aspects of outpatient care and includes discussion of new developments and breakthroughs in medicine.